2018
DOI: 10.3390/agronomy8110264
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seaweed Aqueous Extracts and Compost on Vegetative Growth, Yield, and Nutraceutical Quality of Cucumber (Cucumis sativus L.) Fruit

Abstract: The objective of this research was to evaluate the production and phytochemical quality of cucumber (Cucumis sativus) fruits, in response to the foliar application of different seaweed extracts. This study was carried out under shadow mesh conditions in the autumn–winter agricultural cycle at the Instituto Tecnológico de Torreón, Torreón, Coahuila, Mexico. The experimental design was completely random, using six treatments with six repetitions each. The treatments evaluated were: Macrocystis pyrifera, Bryotham… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 23 publications
(22 reference statements)
5
21
0
3
Order By: Relevance
“…The findings of the present study agree with those of the many earlier studies of Layek et al [1,65], Ashour et al [4], and Hidangmayum and Sharma [66]. Closely related results of increased consumption of N, P, K, and Mg in cucumber (Cucumis sativus) with application of seaweed extracts have been previously recorded [25]. Moreover, TAM application could superiorly differ from the 100% conventional treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the present study agree with those of the many earlier studies of Layek et al [1,65], Ashour et al [4], and Hidangmayum and Sharma [66]. Closely related results of increased consumption of N, P, K, and Mg in cucumber (Cucumis sativus) with application of seaweed extracts have been previously recorded [25]. Moreover, TAM application could superiorly differ from the 100% conventional treatment.…”
Section: Discussionsupporting
confidence: 92%
“…As reported previously, seaweed liquid fertilizers could increase chlorophyll content [20], increase total yield [4], and improve the root system [21]. In conjunction with its rapid and easy handling process, the applicability of seaweed extract foliar spraying has been studied [22], with a focus on stimulating growth and increasing the productivity of some important vegetable crops, such as cucumber [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In general, seaweed extracts enhance plant growth and quality and improve the resistance to climatic changes because they are rich in fatty acids, minerals and polysaccharides [54]. The chemical and biochemical constituents of any seaweed extract act as biostimulants that work synergistically [55,56]. There was a good agreement with the results of previous studies that indicated the beneficial effects of diluted seaweed extracts on plants such as artichoke [15,42].…”
Section: Head Qualitysupporting
confidence: 80%
“…Ten-percent foliar sprays of seaweed extract from the species Macrocystis pyrifera, Grammatophora spp., Bryothamnion triquetrum, Ascophyllum nodosum, and Macrocystis integrifolia, the first two laboratory made and the latter being commercial products 'FulvimaxAT', 'SeaplantAT', and 'GaiaAT', respectively, were tested on greenhouse cucumber grown in sand and vermicompost against a control irrigated with Steiner solution, a standardized nutrient solution employed in agriculture. While the SWEs-treated plants showed a lower fruit size and weight compared to the nutrient-solution irrigated control, the Bryothamnion triquetrum treatments only showed a 7% reduction in fruit weight and an 8.3% reduction in yield [132].…”
Section: Implication Of Biostimulant Substance Treatments On Cucurbit Growth and Yieldmentioning
confidence: 80%